2018
DOI: 10.1111/ppl.12683
|View full text |Cite
|
Sign up to set email alerts
|

GsSLAH3, a Glycine soja slow type anion channel homolog, positively modulates plant bicarbonate stress tolerance

Abstract: Alkaline stress is a major form of abiotic stress that severely inhibits plant growth and development, thus restricting crop productivity. However, little is known about how plants respond to alkali. In this study, a slow-type anion channel homolog 3 gene, GsSLAH3, was isolated and functionally characterized. Bioinformatics analysis showed that the GsSLAH3 protein contains 10 transmembrane helices. Consistently, GsSLAH3 was found to locate on plasma membrane by transient expression in onion epidermal cells. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…The fixation of carbon dioxide in the elongation zone from the bicarbonate buffer leads to the inhibition of root growth (Lee and Woolhouse, 1969). A recent study has reported that a slowtype anion channel homolog in Glycine soja, GsSLAH3, modulates plant bicarbonate stress tolerance (Duan et al, 2018). Heterologous expression of GsSLAH3 in Arabidopsis can increase bicarbonate in shoots, but it does not improve high pH tolerance (Duan et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fixation of carbon dioxide in the elongation zone from the bicarbonate buffer leads to the inhibition of root growth (Lee and Woolhouse, 1969). A recent study has reported that a slowtype anion channel homolog in Glycine soja, GsSLAH3, modulates plant bicarbonate stress tolerance (Duan et al, 2018). Heterologous expression of GsSLAH3 in Arabidopsis can increase bicarbonate in shoots, but it does not improve high pH tolerance (Duan et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has reported that a slowtype anion channel homolog in Glycine soja, GsSLAH3, modulates plant bicarbonate stress tolerance (Duan et al, 2018). Heterologous expression of GsSLAH3 in Arabidopsis can increase bicarbonate in shoots, but it does not improve high pH tolerance (Duan et al, 2018). Therefore, SCaBP3 may be involved in both extracellular pH and HCO 3 2 responses.…”
Section: Discussionmentioning
confidence: 99%
“…An alkaline stress-induced SLAH gene GsSLAH3 , the homologous gene to AtSLAH3 , was identified in the bicarbonate (NaHCO 3 ) stress tolerant G. soja G07256 based on RNA-seq data. Transgenic Arabidopsis over-expressing GsSLAH3 displayed higher tolerance to stress (NaHCO 3 and KHCO 3 ) rather than high pH stress, by increasing accumulation in shoots ( Duan et al., 2017 ). Consistently, under NaHCO 3 treatment, the concentrations in the T-DNA insertion Arabidopsis mutants atslah3-1 and atslah3-2 were relatively lower than WT ( Zheng et al., 2015 ) ( Figure 1B ).…”
Section: Regulation Of Ion Toxicity Under Salt-alkaline Stress In Wil...mentioning
confidence: 99%
“…In soybean, some genetic factors also regulate NaHCO3 rather than pH. For instance, an alkaline stress-induced slow anion channels homolog (SLAH) GsSLAH3 and B transporters GsBOR2 exerted higher tolerance to NaHCO3 and KHCO3 but not to pH ( Duan et al., 2018a ; Duan et al., 2018b ). However, GsBOR2 direct role in K + regulation under NaHCO3 and KHCO3 stress remained unclear.…”
Section: Sustaining Ionic and Ros Homeostasis Under Saline-alkaline S...mentioning
confidence: 99%